(untitled) (Bulletin of Innovative Research, 2026)
Graphics are a system of conventional signs that have been developing since ancient times. It can be said that the graphic image dates back to the great scientists Aristotle and Heraclitus, who lived and created in the centuries BC. There is also information that at the beginning of the 1st century BC, the Greeks used dots located at the bottom, middle or top of the line. Graphic tools have evolved over the years, from simple lines, dots or cave paintings in ancient times, to various alphabets, hieroglyphs, emoji, emoticons, gifs, memes, graphons, ideograms, diagrams, logograms, grammatograms, etc. The article presents definitions of graphics and classifications of its types. Also, in Agatha Christie’s work "The Mysterious Affair at Styles", the state of the heroine is reflected using graphic tools.